Analisis Hubungan K3 Dengan Produktivitas Kerja Karyawan di Pabrik Kelapa Sawit: Literatur Review - Mhd Taupik Sofyan (Yayasan Daarul Huda Kruengmane, 2023)
Occupational safety and health (K3), including one of the maintenance programs in the company. In this study, the design used is Literature Review. The method of searching for article data sources was carried out through the Google Scholar database in the 2019-2023 period to retrieve relevant articles published in Indonesian. Occupational safety and health can have a major effect on employee work productivity. Productive employees have the ability to work, both from the expertise and skills they have.